Effect of Traditional Korean Medicine Treatment Including Acupotomy on the Level of Pain and Quality of Life of Patients with Cervical Herniated Intervertebral Disc: A Retrospective Observational Study - Beom Seok Kim; Ki Jung Sung; Ye Ji Lee; Ju Hyun Jeon; Young Il Kim (MEDrang Inc., 2021)
Background The purpose of this study was to statistically analyze the treatment effect and patient satisfaction of traditional Korean medicine, including acupotomy treatment of cervical herniated intervertebral disc. Methods This was a retrospective study of 22 patients who received traditional Korean medicine including acupotomy treatment amongst all patients diagnosed with cervical herniated intervertebral discs at the Korean Medicine hospital in Daejeon, Korean, from January 01, 2020 to April 30, 2021. The clinical data from patient medical records were statistically analyzed. Results The Numeric Rating Scale, the European Quality of Life 5 Dimensions, and the European Quality of Life Visual Analogue Scale questionnaire scores were each compared before and after traditional Korean medicine treatment, including acupotomy, showed significantly improved scores after treatment (p < 0.001). Out of a total of 22 patients, 11 rated the treatment "very satisfactory" (50%), 5 "satisfactory" (22.7%), 5 "indifferent" (22.7%), 1 "unsatisfactory" (4.5%), and 0 "very unsatisfactory" (0%). Of the total 22 patients, 17 patients (77.3%) were willing to have further treatment, and 5 patients (22.7%) were not willing. Conclusion Traditional Korean medicine treatment including acupotomy was an effective treatment for cervical herniated intervertebral discs. To determine the effect of an individual application (e.g., acupotomy) of traditional Korean medicine treatment for cervical herniated intervertebral disc, a prospective, controlled study is needed.